KEPEMIMPINAN OTENTIK DAN MOTIVASI SANTRI DI LINGKUNGAN PESANTREN - Hariyadi, Ahmad; Fathurohman, Irfai; Fajrie, Nur; Rondli, Wawan Shokib; Wijayanto, Wasis; Shofwani, Siti Aniqoh (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
This study aims to describe the authentic leadership and motivation of santri focusing on the pesantren environment with transparency, integrity, and deep interpersonal relationships, believed to increase santri's sense of satisfaction and enthusiasm for learning. Using a qualitative method with a descriptive approach, data were obtained through in-depth interviews, observation, and document analysis. The main data sources consisted of kiai, santri, and pesantren administrators. The results showed that authentic leadership has a positive effect on santri satisfaction and motivation. KiaiKiyai who applies transparency, exemplary, and attention to the needs of santri succeed in creating a harmonious learning atmosphere, where santri feel valued and more motivated. Authentic leadership also encourages santri to develop Islamic characters who are independent, resilient, and responsible.